IMPACTUL COMPORTAMENTULUI CONSUMATORULUI DIN REPUBLICA MOLDOVA ÎN ELABORAREA STRATEGIEI DE PROMOVARE A UNEI MĂRCI - Antoci, Natalia (CEP USM, 2020)
This article presents the impact of consumer 'behavior in the Republic of Moldova. The purpose of research is to study of the stages of the decision-making process and the influence of product value on consumer behavior. That is why knowledge and explanation of consumer behavior has become an urgent necessity, the to satisfy more needs, more sophisticated, higher quality, aspects that must be taken into account by the manufacturer ignorance of which can produce degrees of imbalance between supply and demand. On the other hand, the increase of purchasing power at the same time as raising the level of education and culture offers the possibility for the buyer.
Keywords: consumer; behavior; subjective knowledge